THE CORRELATION BETWEEN STUDENTS’ VOCABULARY LEARNING STRATEGIES AND THEIR VOCABULARY SIZE - Khatimah, Nur Husnil; Nugroho, Dwi Adi; Mustari, Sri Hariati (English Language, Linguistics, and Culture International Journal, 2022)
The research aimed to finding out the types of vocabulary learning strategies (VLS) used by students of SMK Negeri 4 Makassar, the differences of vocabulary learning strategies used by the students of SMK Negeri 4 Makassar based on their field of study, and whether or not the significant relationship between vocabulary learning strategies and vocabulary size of the students of SMK Negeri 4 Makassar. The research applied correlational research design. Three classes different from three majors; accounting, administration, and tourism, were chosen as the subjects of this research obtained through random sampling technique from the population that consisted of 156 students in the academic year 2016/2017. There were 82 samples in this research. The result of this research was accounting students used metacognitive strategies frequently (m=3.39), administration students tended to use determination strategies (m=3.32), and tourism students applied social strategies frequent (m=3.37), and (3) there was a significant correlation between students’ VLS and vocabulary knowledge based on result where r = .225 categorized as low degree of correlation and p = .042 where p<α (α=.05), it means H0 was rejected. Therefore, the result indicated that VLS used of students of SMK Negeri 4 Makassar had correlation with their vocabulary knowledge. The students used vocabulary learning strategies respectively from the most frequent to the least frequent; they are metacognitive strategies, determination strategies, social strategies, memory strategies, and cognitive strategies.